Editorial da Revista Digital do Laboratório de Artes Visuais - Oliveira, Marilda Oliveira de; Charréu, Leonardo Augusto Verde Reis; Queiroz, João Paulo (Revista Digital do LAV, 2015)
Editorial da Revista Digital do LAV